Microbial metabolites short chain fatty acids, tight junction, gap junction, and reproduction: a review - Fu, Lulu; Wang, Min; Li, Dan; Ma, Shuai; Zhang, Fuliang; Zheng, Lianwen (Frontiers in Cell and Developmental Biology, 2025)
The gut microbiota, comprising trillions of bacteria, fungi, and viruses, exists in symbiosis with the host. As the largest microbial ecosystem in the human body. The gut microbiota not only shapes the homeostasis of the intestinal microenvironment through gut-derived metabolites but also exerts regulatory effects on the functions of diverse tissues and organs throughout the body via the intricate “gut-distal organ axis” mechanism. Short chain fatty acids, such as acetic acid, propionic acid and butyric acid are high abundance intestinal metabolites, not only influence the intestinal barrier by regulating tight junction proteins, but also affect intestinal peristalsis by regulating gap junction proteins. These microbial metabolites may also play a important role in the formation and maintenance of the key barriers of the reproductive system, such as the ovarian blood follicle barrier, the testicular blood-testis barrier, and the endometrial epithelial barrier. In reproductive system, Gap junction-mediated intercellular communication, facilitated by connexins, proves essential in germ cell maturation, embryo implantation, and spermatogenesis. The dysregulation of these microbial metabolites leading to abnormal tight junction and gap junction protein functions provides novel perspectives for understanding the pathogenesis of reproductive disorders such as polycystic ovary syndrome and premature ovarian failure. This review systematically elucidates the molecular networks through which short-chain fatty acids regulate tight and gap junction proteins, highlighting their potential roles in reproductive physiology.